Species composition of euglenoids belonging to the family euglenaceae from Lak lake, Dak Lak province - Son, Dao Thanh; Tung, Nguyen Thanh (Academia Journal of Biology, 2013)
Euglenophytes are among the most diverse eukaryote algae and not much studied in the world in general and in Vietnam in particular. In this study, diversity of the three euglenophytes’ genera Lepocinclis, Phacus andTrachelomonas was investigated from Lak lake, Dak Lak province. The sampling was conducted in September 2002 (middle of rainy season), January 2003 (trans-season period) and March 2003 (middle of dry season) and samples were taken at nine sites in the lake. The results showed that 48 taxa of the three genera were observed of which diagnosis of 14 newly record species were given. Viz.,Lepocinclis globosa, L. marssonii v. sinensis, L. striata, Phacus landekiensis, P. pseudoswirenkoi, P. stokesii v. minor, P. swirenkoi, P. trypanon, Trachelomonas armata v. rangpurense, T. cf. dubia, T. planctonica v. oblonga, T. pseudobulla v. bulloides, T. pulcherrima v. minor and T. torosa. This record from Lak Lake makes a contribution to the understanding on the biodiversity of Euglenoids in particular and micro flora of Vietnam in general.